Establishing the cultural identity of the west in the early Cold War: a conceptual approach - Papadimitriou, Despina (Historein, 2014)
This article examines the conceptual features of the semantic field constructed in the west in the early Cold War and the basic concepts and notions that framed the Cold War ideologically in the west, such as democracy versus totalitarianism; universal freedom and freedom of the spirit versus totalitarian oppression; welfare democracies versus poverty and exploitation; and Christianity, family and traditions versus communism. The transnational character of the antitotalitarian discourse under investigation followed the linear border of the universal ideological division as opposed to the horizon of the various enduring realities in the domestic scene.